Mouriri elliptica: Validation of gastroprotective, healing and anti-Helicobacter pylori effects - Moleiro, Fabio Cruz [UNESP]; Andreo, Marcio Aparecido [UNESP]; dos Santos, Raquel de Casia [UNESP]; Moraes, Thiago de Mello [UNESP]; Rodrigues, Clenilson Martins [UNESP]; de Andrade Carli, Camila Bernardes [UNESP]; Mascia Lopes, Flavia Cristine [UNESP]; Pellizzon, Claudia Helena [UNESP]; Carlos, Iracilda Zeppone [UNESP]; Bauab, Tais Maria [UNESP]; Vilegas, Wagner [UNESP]; Hiruma-Lima, Clélia Akiko [UNESP] (Elsevier B.V., 2009)
Ethnopharmacological relevance: Mouriri elliptica Martius (Melastomataceae) is species reputed in folk medicine to heal gastric ulcer and gastritis.Aim of the study: Methanolic extract (ME) and ethyl acetate fraction (EAF) from leaves of Mouriri elliptica were evaluated for their gastroprotective, healing, immunological, toxicological and anti-Helicobacter pylori activities.Material and methods: The gastroprotective action of ME and EAF was evaluated in rodent experimental models and to elucidate mechanisms of action, the antisecretory action, involvements of NO, SH, PGE(2), anti-Helicobacter pylori action of ME was evaluated. We also used immunohistochemical (PCNA and COX-2) and immunomodulatory (murine peritoneal macrophages) assays to evaluate Mouriri elliptica effects.Results: ME present gastroprotective action without antisecretory effect. Otherwise, ME showed anti-Helicobacter pylori action (MIC = 0.025 mu g/mL) and was able to inhibit NO production by macrophages. This species also accelerate the healing of ulcerated gastric mucosa by stimulating proliferation factors (PCNA), COX-2 and maintained basal PGE(2) level independent action of NSAID in gastric mucosa. The phytochemical investigation showed that this species possesses phenolic acid derivatives, acylglycoflavonoids and condensed tannins which probably influenced their pharmacological action.Conclusion: All these results suggest the efficacy and safety of Mouriri elliptica in combating and healing gastric ulcer. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Mouriri elliptica; Melastomataceae; Antiulcer; PCNA; COX-2; Prostaglandin E(2)